Fahimi’s racerunner, a new species of the genus Eremias Fitzinger, 1834 (Sauria: Lacertidae) from Iran - Mozaffari, Omid; Ahmadzadeh, Faraham; Saberi-Pirooz, Reihaneh (Zootaxa, 2020)
We describe a new species of Lacertid lizard of the genus Eremias from the border of the northeastern side of Markazi Province to the western side of Tehran Province in Iran. Eremias fahimii sp. nov. is part of the Eremias subgenus (or morphotype) by virtue of lacking lateral fringes on the fourth toe, having movable eyelids, a lower nasal shield that rests on two supralabials, and ventral plates arranged in oblique longitudinal rows. It can be further differentiated from previously described species assigned to this morphotype by the absence of distinctly keeled upper caudal scales, gular scales that do not extend to the second inframaxiallary scales, shape and relative size of frontoparietals, parietal and parietals, scale counts and absence of lateral color ocellus. In addition, the molecular phylogeny of the most common Iranian racerunners including Eremias fahimii sp. nov. was studied using mitochondrial Cytochrome b (Cyt b) and 12S ribosomal RNA (12S) genes. Our results support the validation of the new species which depicts a sister group relationship to E. persica. Of the 20 species of Eremias known from Iran, E. fahimii sp. nov. is the seventh endemic species along with E. andersoni, E. isfahanica, E. lalezharica, E. kavirensis, E. montana and E. papenfussi. Despite the fact that up to now E. fahimii sp. nov. is only known from the type locality, it is highly probable that it also occurs in Tehran, Alborz, Qom, Qazvin and Zanjan Provinces due to topological characteristics and habitat similarities in these areas.